PENGEMBANGAN PERANGKAT PEMBELAJARAN TERPADU BERBASIS KEARIFAN LOKAL UNTUK KELAS III SEKOLAH DASAR DI KABUPATEN MADIUN - Tryanasari, Dewi; Riyanto, Edy; Mursidik, Ellys Mersina (Premiere Educandum, 2013)
This Â research Â is Â attempted Â to: Â  (1) Â  describe Â  the Â  steps Â  of Â  theÂ development of Â local-wisdom-based integrated teaching media; (2) describe the quality of the local-wisdom-based teaching media; (3) describe the implementation of local-wisdom-based teaching media; and (4) describe the impacts of the implementation of local-wisdom- based Â teaching Â media. Â The Â method Â of Â the Â research Â is Â Dick Â and Careyâs model of Research and Development, which frames the development of teaching instruments. The objects of the research are the developed teaching instruments, and the subjects are 10 students of Balerejo II and 30 students of Balerejo IV. The data are analyzed descriptively by using observation record for the teaching events, and appraisal technique for the teaching instruments. The results of the analysis Â show Â that: Â (1) Â the Â teaching Â instruments Â can Â be Â well- developed being measured by the Dick and Careyâs model, which are scored as: 4.22 for Lesson Plan, 4.5 for Media, 4.14 for Teacherâs Guide, 4.26 for Book, and 3.96 Student Work Sheets; (2) the quality of the local-wisdom media is good; (3) the implementation of the model is Â good, Â by Â 89.75% of Â the Â application Â of Â lesson Â plan Â in Â the fisrt meeting and 91.01% in the second meeting. Studentsâ Â response is good, by 40.6 (agree) and 41.2 (very much agree). Teacherâs activities are good in response to the suggested activities of the lesson plan. Studentsâ activities are good with 99.41% of the activities are relevant to lesson plan, and the average achievement raise significantly. (4) Supporting factors cope with studentsâ experience in learning amusingly without disturbing contact to their mates. Some disadvantagous factors can be resolved by teacherâs improvisations. Key words:Â Â Teaching Media Development, Integrated Teaching andLearning